Effects of pre-chilling potassium nitrate and post-chilling hydrogen cyanamide application on carbohydrate and water dynamics of ‘Housui’ Japanese Pear spur buds during dormancy under mild winter conditions - HORIKOSHI, Humberto Mitio; SEKOZAWA, Yoshihiko; SUGAYA, Sumiko (Revista Teste SPGG, 2016)
Japanese pear (Pyrus pyrifolia Nakai) trees were treated with potassium nitrate (KNO3) before the onset of chilling and hydrogen cyanamide (CH2N2) after the trees had accumulated 600 chilling hours (CH) to determine the effects on bud dormancy release, carbohydrate dynamics, and water content. For the carbohydrate and water content analyses, Japanese pear spur buds were collected after 0, 300, and 600 CH, and after the accumulation of 2000, 4000, 6000, and 8000 growing degree hours (GDH) during the dormancy period. Bud burst and flowering were hastened by both KNO3 and CH2N2 application, and both chemicals affected carbohydrate and water dynamics during dormancy. Sucrose concentration tended to increase during the chilling period, and to decrease under forcing conditions. Hexose concentrations increased in buds treated with KNO3, CH2N2, or both, and were associated with advances in bud burst. Sorbitol concentration decreased early in buds treated with CH2N2, suggesting rapid sorbitol catabolism. Water content gradually increased under forcing conditions in all buds, although those treated with both KNO3 and CH2N2 exhibited the highest values. Accordingly, we recommend the use of KNO3 and CH2N2, before and after chilling, respectively, to promote the release of bud dormancy and increase bud burst rate in ‘Housui’ Japanese pear grown in regions with mild winter conditions.